A finite element analysis approach to predict constraint benefits to ductile tearing initiation toughness. (November 2022) - Beswick, Jack; James, Peter; Pellereau, Ben
Highlights: It is possible to estimate a constraint based, ductile tearing initiation toughness enhancement using numerical procedures alone. The procedure predicts the toughness benefit using Rice and Tracey contour scaling approaches. The procedure offers good agreement with test data and GTN modelling of similar scenarios. A lower bound toughness benefit is applicable for a range of materials. Abstract: This paper provides a novel approach to define the parameters to derive effective ductile tearing initiation toughness curves for a range of materials under low constraint conditions, using finite element analysis alone. This eliminates the need for extensive low constraint testing programmes. The curves are provided for four nuclear steam raising plant materials, and a generic, lower-bound curve is also defined. The lower bound curve would allow an increased fracture toughness to be used in assessments where defects could be shown to be at low in-plane constraint ( Q  < 0), and within the bounds of the materials examined here. The curves have been calculated by defining the loads, quantified by the J integral, at which areas of material ahead of the crack tip, in 2D Single Edge Notched Bend specimen finite element models, enclosed by contours defined by a critical void size, are equal. By determining the load at high constraint at which the contour encloses a specific area, and obtaining the load at which the area is equal at low constraint, it has been possible to determine the toughness curves by assuming failure occurs when the areas enclosed by the contours are equal. It is shown that the shape of the toughness curve is largely independent to the critical void size ratio, defined using the Rice and Tracey parameter, and the value used for the high constraint toughness. This provides confidence in the method, alongside comparison against relevant initiation toughness test data, and similar modelling incorporating the GTN local approach.